Harmonizing the Principle of Judicial Pardon in Indonesia's Positive Law to Achieve Dignified Justice: Harmonisasi Asas Permaafan Hakim (Judicial Pardon) Dalam Hukum Positif Indonesia Untuk Mencapai Keadilan Yang Bermartabat - Krisnamurti, Hana (Faculty of Law, Universitas Pasundan, 2025)
Law No. 1 of 2023 on the Indonesian Criminal Code introduces the principle of Judicial Pardon under Article 54(2), reflecting a progressive effort to advance substantive justice in Indonesia’s criminal justice system. However, its implementation remains problematic because procedural criminal law does not provide a clear mechanism for applying judicial pardon in practice. This study examines the concept and significance of judicial pardon from the perspective of dignified justice and proposes strategies to harmonize its regulation within the Criminal Code, the Criminal Procedure Code, and the Law on Judicial Power. Using a descriptive-analytical method, this research focuses on judicial pardon as regulated in the Criminal Code and applies qualitative juridical analysis to interpret the findings systematically. The results show that judicial pardon grants judges discretion to prioritize justice over legal certainty, yet such discretion requires procedural safeguards to ensure consistency and accountability. A comparison with the Dutch legal system confirms the importance of detailed procedural rules to prevent arbitrary application. This study recommends harmonization through: (1) technical guidelines in a Draft Government Regulation outlining procedures and parameters for judicial pardon; (2) formal recognition of judicial pardon as a type of judicial decision in Law Number 20 of 2025 on Criminal Procedure Law; and (3) revision of the Law on Judicial Power to establish ethical and technical standards for judges. Such harmonization is essential to build a criminal justice system that upholds dignified justice.